A eukaryotic-type signalling system of Pseudomonas aeruginosa contributes to oxidative stress resistance, intracellular survival and virulence - Goldová, Jana; Ulrych, Aleš; Hercík, Kamil; Branny, Pavel (BMC genomics, 2011)
BACKGROUND: The genome of Pseudomonas aeruginosa contains at least three genes encoding eukaryotic-type Ser/Thr protein kinases, one of which, ppkA, has been implicated in P. aeruginosa virulence. Together with the adjacent pppA phosphatase gene, they belong to the type VI secretion system (H1-T6SS) locus, which is important for bacterial pathogenesis. To determine the biological function of this protein pair, we prepared a pppA-ppkA double mutant and characterised its phenotype and transcriptomic profiles. RESULTS: Phenotypic studies revealed that the mutant grew slower than the wild-type strain in minimal media and exhibited reduced secretion of pyoverdine. In addition, the mutant had altered sensitivity to oxidative and hyperosmotic stress conditions. Consequently, mutant cells had an impaired ability to survive in murine macrophages and an attenuated virulence in the plant model of infection. Whole-genome transcriptome analysis revealed that pppA-ppkA deletion affects the expression of oxidative stress-responsive genes, stationary phase σ-factor RpoS-regulated genes, and quorum-sensing regulons. The transcriptome of the pppA-ppkA mutant was also analysed under conditions of oxidative stress and showed an impaired response to the stress, manifested by a weaker induction of stress adaptation genes as well as the genes of the SOS regulon. In addition, expression of either RpoS-regulated genes or quorum-sensing-dependent genes was also affected. Complementation analysis confirmed that the transcription levels of the differentially expressed genes were specifically restored when the pppA and ppkA genes were expressed ectopically. CONCLUSIONS: Our results suggest that in addition to its crucial role in controlling the activity of P. aeruginosa H1-T6SS at the post-translational level, the PppA-PpkA pair also affects the transcription of stress-responsive genes. Based on these data, it is likely that the reduced virulence of the mutant strain results from an impaired ability to survive in the host due to the limited response to stress conditions.
Keywords: oxidační stres; bakteriální RNA; transkriptom; Cell Line; fenotyp; protein-serin-threoninkinasy; Phenotype; Bacterial Proteins; mikrobiální viabilita; virulence; Protein Serine-Threonine Kinases; salát (hlávkový); Lactuca; Transcriptome; regulace genové exprese u bakterií; Virulence; Gene Deletion; Oligonucleotide Array Sequence Analysis; Oligopeptides; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Animals; Pseudomonas aeruginosa; Microbial Viability; zvířata; Genetic Complementation Test; makrofágy; bakteriální proteiny; testy genetické komplementace; myši; delece genu; buněčné linie; Mice; Macrophages; Oxidative Stress; RNA, Bacterial; oligopeptidy; Gene Expression Regulation, Bacterial